Kekerasan emosional menyebabkan kenakalan pada remaja - Alfianur Alfianur; Ezalina Ezalina; Elfiza Fitriami (Holistik Jurnal Kesehatan, 2020)
Adolescent emotional distress and misbehaviorBackground: Emotional distress is an act that demeans the child through condemnation of words that continues to neglect the child, isolate the child from the environment and social relationships, blame the child continuously and emotional abuse is usually always followed by other violence. Emotional distress can cause physical and psychological trauma from mild to severe intensity, so that it can lead to misbehavior. Misbehavior is evil or naughty behavior committed by adolescents so that it irritates oneself and others.Purpose: Determining the correlation between adolescent emotional distress and misbehaviorMethod: A quantitative study with a correlation research design and the approach used is cross sectional. The sample in this study were 30 teenagers. The study was conducted at the Technical Implementation Unit of Social Services for Adolescent Development Marsudi Putra Tengku Yuk Pekanbaru. The measuring instrument used was a questionnaire of emotional distress and misbehavior. The analysis used univariate and bivariate using the Chi-square test.Results:The analysis of the study obtained p value 0.01 <0.05, which means there is a correlation between emotional distress and misbehavior and the risk of adolescents misbehavior as much as 10.8 times.Conclusion: There is a correlation between emotional distress and misbehavior at the Technical Implementation Unit of Social Services for Youth Development Marsudi Putra Tengku Yuk Pekanbaru.Keywords: Emotional distress; Misbehavior; AdolescentPendahuluan: Kekerasan emosional merupakan tindakan yang merendahkan anak melalui kecaman kata-kata yang berlanjut dengan melalaikan anak, mengisolasi anak dari lingkungan dan hubungan sosialnya, menyalahkan anak terus menerus dan kekerasan emosional biasanya selalu diikuti dengan kekerasan lain. Kekerasan emosional dapat menyebabkan trauma fisik dan psikologis dari intensitas ringan-berat, sehingga dapat menimbulkan munculnya kenakalan remaja. Kenakalan remaja adalah perilaku jahat atau nakal yang dilakukan oleh remaja sehingga mengganggu diri sendiri dan orang lain.Tujuan: Untuk mengetahui hubungan antara kekerasan emosional dengan kenakalan remaja.Metode: Penelitian kuantitaf dengan desain penelitian korelasi dan pendekatan yang digunakan adalah cross sectional. Sampel dalam penelitian ini sebanyak 30 orang remaja. Penelitian dilakukan di Unit Pelaksanaan Teknis Pelayanan Sosial Bina Remaja Marsudi Putra Tengku Yuk Pekanbaru. Alat ukur yang digunakan adalah kuesioner kekerasan emosional dan kenakalan remaja. Analisis yang digunakan univariat dan bivariat menggunakan uji Chi-square.Hasil: Didapatkan p value 0,01 < 0,05 yang artinya ada hubungan antara kekerasan emosional dengan kenakalan remaja dan risiko remaja dengan kekerasan emosional melakukan kenakalan remaja sebanyak 10,8 kali .Simpulan: terdapat hubungan antara kekerasan emosional dengan kenakalan remaja di Unit Pelaksanaan Teknis Pelayanan Sosial Bina Remaja Marsudi Putra Tengku Yuk Pekanbaru.